2020
DOI: 10.1111/ijfs.14523
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ultra‐homogenisation and ultrasound for extraction of phenolic compounds from teff (Eragrostis tef (Zucc.))

Abstract: This study investigated the effect of the solvent composition on the extraction of phenolic compounds from teff grains and compared the efficiency between the techniques homogeniser‐assisted extraction (HAE) and ultrasound‐assisted extraction (UAE). The solvents used were water, ethanol and methanol, and the response analysed was the total phenolic content (TPC). The quantitative profile of polyphenols extracted was also determined by ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐TQD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Viell et al. (2020) reported in their study that tef grains contain a considerable quantity of phenolic compounds and flavonoids as potential antioxidants, and protocatechuic acid, p ‐coumaric acid, rutin, and quercetin are the main polyphenols. In addition, it is thought that with the increase of acidity occurred during fermentation, probably bound phenolic compounds become free and contribute to total phenolics and antioxidants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viell et al. (2020) reported in their study that tef grains contain a considerable quantity of phenolic compounds and flavonoids as potential antioxidants, and protocatechuic acid, p ‐coumaric acid, rutin, and quercetin are the main polyphenols. In addition, it is thought that with the increase of acidity occurred during fermentation, probably bound phenolic compounds become free and contribute to total phenolics and antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hager et al (2012), the total phenolic content (TPC) in teff is higher than that in other grains, including wheat, rice, oats, sorghum, corn, quinoa, and amaranth. Viell et al (2020) 319.6, 2,423.2, 2,657.0, 2,800.8, 2,883.2, and 2,979.3 mgGAE/kg, respectively. They found that the total phenolic content increased as the amount of oat flour increased.…”
Section: Nutritional Properties Of the Tarhana Samplesmentioning
confidence: 96%
“…Beside enzyme inactivation, HIU has been proven to affect the extraction of bioactive compounds from different plant materials, such as potato wastes, teff, wheat chaff, and dried distiller's grain (Đorđević & Antov, 2017;Izadifar, 2013;Torres & Domínguez, 2020;Viell et al, 2020) as well as arabinoxylans from WB . Also, ultrasound pretreatment improves an enzymolysis efficiency of wheat gluten and the angiotensin-I converting enzyme inhibitory activity of hydrolysates (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For both UAE and HAE, the sample was maintained at 30°C employing an ultra-thermostatic bath (Quimis -Q214 M, Diadema, SP, Brazil). The extracts were centrifuged (Centrifuge NT 825, New Technique, Piracicaba, Brazil) at 4,000 rpm (1,430 g) and 4°C for 15 min (Viell et al, 2020). Then, extracts were vacuum filtered repeatedly with filter paper (Quanty, 8 µm porosity, Adria laboratories-Londrina-PR) and vacuum pump (model 121-Prismatec), until the obtainment of translucent permeates.…”
Section: Extraction Proceduresmentioning
confidence: 99%